138 We Tried This At Home – Safety Analysis and Outcome of Community Resource Services. (16th March 2021) - Norris, S; Kumar, A; Carney, K; Jones, A; Sweeting, O; Kitson, J
Abstract: Introduction: There are several data sets published for acute frailty services in hospital but there is a lack of supporting data in the emerging field of Intermediate Care. Gwent has well-established Community Resource Teams (CRT) that were set up as "Hospital at Home" services. The objective being to treat frail, acute or sub-acute medically ill patients in their own environment by a consultant-led hospital-like team using a Comprehensive Geriatric Assessment. Although "Hospital at Home" services are often preferred by the patient and are in-line with Health board strategies "Care Closer to home" and "Clinical Futures"; it is important to ask ourselves whether we are able to deliver clinical care in the community safely? Method: One year of data from 2018 was extracted from the CRT Portal, analysed and then validated by the health board's performance teams. From the established data set, origin of referrals and discharge outcomes were identified. Finally, at 28 days of discharge from Gwent CRTs mortality and hospital admission rates were examined. Results: 4, 308 out of 5, 395 referrals (85%) were accepted to Gwent CRTs of which 59.60% (2, 863) referrals were from primary care and 33.54% (1, 445) were from secondary care. Our admission rates to secondary care services were 15.27% (658) whilst mortality rate was 3.92% (169). After successful medical management from Gwent CRTs of 3, 481 patients in their own place of residence, 28 day hospital admission rate was 13.84% (482) whilst 28 day mortality rate (expected and unexpected) was 6.89% (240). Conclusion: Although no equivalent data is currently available for comparison, a significant number of patients can be medically managed in their own place of residence. More than 80% of patients did not require hospital admission whilst mortality rates were encouraging. Further future re-evaluation of our service performance and its value is required.